Mechanisms for the Invasion and Dissemination of Salmonella - Qiao Li (Canadian Journal of Infectious Diseases and Medical Microbiology)
Salmonella enterica is a gastroenteric Gram-negative bacterium that can infect both humans and animals and causes millions of illnesses per year around the world. Salmonella infections usually occur after the consumption of contaminated food or water. Infections with Salmonella species can cause diseases ranging from enterocolitis to typhoid fever. Salmonella has developed multiple strategies to invade and establish a systemic infection in the host. Different cell types, including epithelial cells, macrophages, dendritic cells, and M cells, are important in the infection process of Salmonella. Dissemination throughout the body and colonization of remote organs are hallmarks of Salmonella infection. There are several routes for the dissemination of Salmonella typhimurium. This review summarizes the current understanding of the infection mechanisms of Salmonella. Additionally, different routes of Salmonella infection will be discussed. In this review, the strategies used by Salmonella enterica to establish persistent infection will be discussed. Understanding both the bacterial and host factors leading to the successful colonization of Salmonella enterica may enable the rational design of effective therapeutic strategies.